(untitled) (GAIMS Journal of Medical Sciences, 2024)
An elderly female presented with the complaint of a right sided breast lump since six months, found to be Invasive Ductal Carcinoma (IDC) of the Right Breast. Examination also revealed another lesion of suspected Basal Cell Carcinoma (BCC) in the same region, which was later confirmed by histopathological examination. Both these lesions were excised during the same procedure of Modified Radical Mastectomy. Review of literature of this rare coexistence showed no such documentations from India. Genetic basis for the same was reviewed, but could not be evaluated in our patient.